INCREASING SUSTAINABILITY OF FOOD PRODUCTION AND ENSURING HUMAN HEALTH THROUGH AGRICULTURE DIGITALIZATION - Stoian, Mirela; Dobre, Iuliana; Popescu, Cristian George; Vasile, Marius Cosmin; Dimitriu, Anton- Theodor; Ion, Ana (Economics of Agriculture, 2022)
Ensuring safe food for a growing population is a challenge for agriculture. The current systems of intensive agriculture are based on important allocations of factors of production per unit area, like chemical fertilizers and pesticides, allocated in order to stimulate production. In doing so, food security is ensured, by obtaining high yields per hectare, but chemical residues may remain in food and human health is jeopardised. The aim of this research is to identify the role of digitalization in agriculture in balancing the binomial food security-organic farming, starting from the premise that smart agriculture has a signifcantly lower negative impact on the environment and human health compared to the conventional agricultural system. The relevance of research lies in raising awareness of the importance of smart agriculture in providing agricultural products obtained in accordance with the principles of sustainable development and moreover integrating it into policies and actions at all levels: individual, local, national and global.